An identity for a class of arithmetical functions of several variables - Pentti Haukkanen (International Journal of Mathematics and Mathematical Sciences)
Johnson [1] evaluated the sum ∑d|n|C(d;r)|, where C(n;r) denotes Ramanujan's trigonometric sum. This evaluation has been generalized to a wide class of arithmetical functions of two variables. In this paper, we generalize this evaluation to a wide class of arithmetical functions of several variables and deduce as special cases the previous evaluations.